DIDACTIC CAPABILITIES OF DIGITAL PLATFORMS IN SUPPORTING STUDENTS WITH SPECIAL NEEDS IN PRIMARY EDUCATION - Abdunazarova Zebiniso Khudoyshukurovna (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article analyzes the didactic potential of digital platforms in the process of supporting students with special needs in the primary education system from a scientific, theoretical and practical perspective. The importance of an individual approach, differentiated education, multimodal teaching and adaptive technologies in inclusive education is substantiated. The role of digital tools in the context of the principles of inclusive education put forward by UNESCO and UNICEF is also revealed. The research results show that digital platforms have a positive impact on the cognitive activity, motivation and social adaptation of students with special needs.